2005
DOI: 10.1680/macr.2005.57.5.261
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of reinforcement corrosion in concrete and its effects on structural deterioration

Abstract: Studies of the most recently published literature reveal that the current state of research on corrosion propagation in reinforced concrete and its effects on structural deterioration remains unsatisfactory. This is in spite of extensive and intensive research on reinforcement corrosion in concrete for the past three decades or so. This paper presents results produced from an experimental programme designed to investigate the propagation of chloride-induced reinforcement corrosion in concrete and its effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…e investigation of corrosion effect on bond between steel reinforcement and concrete has been studied by many researchers [14][15][16][17]. Li and Zheng [17] showed that the mechanical degradation of bonding is affected by a number of factors such as rebar geometry, its surface profile, concrete composition, compressive strength of concrete, and cover thickness c. Maslehuddin et al [18] showed that on reinforced concrete specimens without stirrups, even though low corrosion damage of steel temporarily improves bond strength, rapid degradation takes place with the development of corrosive phenomena. Respectively, Auyeung [19] stated that on reinforced concrete specimens without stirrups, the corrosive factor dramatically affects bonding, since only 2% of the cross-sectional loss of the reinforcement bar can lead to up to 80% reduction in bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…e investigation of corrosion effect on bond between steel reinforcement and concrete has been studied by many researchers [14][15][16][17]. Li and Zheng [17] showed that the mechanical degradation of bonding is affected by a number of factors such as rebar geometry, its surface profile, concrete composition, compressive strength of concrete, and cover thickness c. Maslehuddin et al [18] showed that on reinforced concrete specimens without stirrups, even though low corrosion damage of steel temporarily improves bond strength, rapid degradation takes place with the development of corrosive phenomena. Respectively, Auyeung [19] stated that on reinforced concrete specimens without stirrups, the corrosive factor dramatically affects bonding, since only 2% of the cross-sectional loss of the reinforcement bar can lead to up to 80% reduction in bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion Effect on Bond Loss between Steel and Concrete DOI: http://dx.doi.org /10.5772/intechopen.94166 Besides corrosion phenomenon, the aspects of steel -concrete adhesion depend to a high extent on numerous parameters related to both steel and concrete, namely steel bar geometry, concrete strength and confinement due to transverse reinforcement and concrete cover thickness [23]. The influence of compressive concrete strength on bond behavior of RC specimens has been studied by Abosrra et al [24] and Zandi and Coronelli [25].…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of RC structures caused by steel corrosion is a serious problem (Hostis et al 2011;Li and Zheng 2005). Damage caused by the steel corrosion may be significant in civil R.C.…”
Section: Introductionmentioning
confidence: 99%